PEMBERIAN KOMBINASI PUPUK ORGANIK CAIR DAN BIOSTIMULAN TERHADAP PERTUMBUHAN TANAMAN BROKOLI (Brassica Oleraceae var. italica) - Ashari, Asri Mulya; Purwaningsih, Purwaningsih (Universitas Gunadarma, 2024)
The high plains are typically home to broccoli plants. The discovery of a new variety of broccoli plants for the lowlands is a gift to the communities in the lowlands. Sustainable crop cultivation efforts on broccoli plants are highly needed today, given the condition, which has been heavily degraded due to the continuous use of synthetic fertilizer without being mixed with the return of organic material into the soil. Another factor is to guarantee the condition of the crops obtained. The research is aimed at obtaining the best combination of liquid organic fertilizer and bio stimulants. This study uses an experimental method with a complete random design consisting of A = POC 150 ml/l + 4 ml, B = 200 ml + 3 ml, C = 250 ml/l + 2 ml, and D = 300 ml/LL + 1 ml. With a multiplication of 5, with the number of samples in this study, there were 4 plants. Observations are performed on variables such as plant height, number of leaves, flower diameter (crop), and fresh flower weight (crop). The results of the study show that the administration of liquid organic fertilizer in combination with bio stimulants boosts the growth of broccoli crops. at a concentration of 250 ml + 2 ml is an effective combination for plant growth, especially for plant height and weight of fresh broccoli carcasses, but not an effective dose for leaf formation.